What kind of procedural rules should be used in the proceedings based on Article 33 Sec. 6 of Hunting Law - Kościelniak-Marszał, Miłosz (The Opole Studies in Administration and Law, 2017)
Under art. 33 it. 6 of Hunting law cases of different nature are heard before a regional court. It is the subject matter of specific proceedings that is decisive in determining which procedural regulations will apply as the above provision refers to different legal relations. The first one refers to the membership in the Polish Hunting Association, which is granted in a way that allows us to recognize it as a civil law occurrence, and therefore the request before a common court for the protection of the membership may be considered a civil action. The second one is related to disciplinary liability which due to repressive nature of sanctions falls within penal liability in its broad sense. In this case, the proceedings before a common court exercised as a result of making an appeal against the decision ending disciplinary proceedings within the structures of the Polish Hunting Association constitute continuation of the disciplinary procedure. The nature of this liability calls for the court appeal control to be conducted on the basis of the same rules pertaining to the law of criminal procedure, on which disciplinary proceedings within the organization were based, and for the procedure ensuring the defendant as far-reaching proceedings security as possible to be applied.